Propranolol and infantile hemangiomas: Outcome from a tricentric study. (January 2023) - Benetton, C.; Pace, MR. Di; De Corti, F.; Cimador, M.; Gamba, P.; Midrio, P.
Abstract: Introduction: The introduction of propranolol as systemic therapy for infantile hemangiomas (IH) has changed the natural history of these tumors. Cases presenting with ulceration, functional limitation, and visceral or life-threatening localization are excellent indications to medical therapy. The aim was to report the medium term follow-up after the introduction of propranolol in 3 referral centers with particular attention to outcome and surgical treatments. Materials and methods: In the period 2011–2018 348 patients underwent systemic therapy with propanolol at a mean age of 3.5 months (range 1–10). The indications to begin the treatment were: visceral localization (10, 6%), ulceration (20%), risk of severe esthetic impairment (27%), and peri‑orifices localization (42.4%). Results: The minimum follow-up was 1 year. Propranolol was administered for a mean of 11 months (range: 6–19) and in 22 cases it was resumed for extra 4.5 months due to rebound. Overall, 97.4% responded to therapy without severe side effects. Seven patients underwent surgery and 9 laser therapy . Twenty-four cases are scheduled for surgery for evident inesthetisms and 4 will undergo laser therapy to complete the treatment. Conclusions: The use of propranolol has considerably decreased the surgical indications for IH, improved the esthetic and functional outcome, and simplified the definitive surgical treatment. The response rate to therapy is very high and in case of failure both laser and surgery are still very effective. The correct diagnosis, early starting, and adequate duration of therapy are key factors for the success of treatment.